IS THE CURSE OF NATURAL RESOURCES OCCURING IN INDONESIA? - Joko Tri Haryanto (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2018)
Theories explain the occurrence of natural resource curse phenomenon as a the conditions in a country has an abundance of mining sector but unsustainable patterns of development. In case of Indonesia, several studies conducted to measure natural resource curse also occurs during decentralization era. Therefore, this research conducted by analyze the performance of APBD in mining areas. By using share analysis, the highest area is East Kalimantan Province, while the lowest is NTT Province. Meanwhile, from growth, the highest area is West Java and the lowest category is Banten Province. From the quadrant analysis, four areas are in the quadrant I, seven areas in quadrant II, six areas in quadrant III and most areas in quadrant IV. This massive number of mining areas in quadrant IV shall inflict a serious note for the Central Government, could be an early indication of the emergence of natural resource curse in Indonesia.